STUDI STRATIGRAFI SEKUEN DALAM FORMASI PULAU BALANG DI LAPANGAN WAILAWI, CEKUNGAN KUTAI, KALIMANTAN TIMUR - SULEIMAN, ARMEIN
The present of oil which have not been exploited and phenomenon of total production gas that higher than its estimated reserve in Wailawi gas field are interesting petroleum geology features to be analysed. With sequence stratigraphy concept approach which is not simply rely on lithostratigraphic correlation is expected that the relation of sedimentary rocks and distribution pattern of reservoir are better understood naturally. This study is using logs data (completion log and mudlog), biostratigraphic data and seismic data. Observation and analysis that performed in this research is started by performing micropaleontology analysis to interpret depositional environment and getting age of observed section, and seismic facies analysis. Further more is performing a model of sequence stratigraphy by determining genetic unit of sedimentary package based on integrating sedimentology interpretation from log data and cuttings and interpretation of depositional environment (bathymetric) from foraminifera fossil that supported by interpretation of seismic facies reflection pattern. Finally, is performed wells correlation to define depositional sequence including its system tracts inside. Result of analysis mentioned that depositional sequence within observed section of Pulau Balang Formation has Early Miocene age. Totally there is five depositional sequence have been identified, each consist of three system tracts i.e. lowstand, transgressive and highstand. It is believed that Pulau Balang Formation is dominated by marine sediment which intercalated by deltaic deposits. Reservoir rocks which proven of hydrocarbon oil is located within lowstand system tract LST-4 of Sequence-4. These sandstones are distributary channel deposit that coalesced with mouth bar deposit of wave dominated delta type of deltaic system. Based on result of study is believed there are potential hydrocarbons trapped stratigraphically, especially in westward area from Wailawi field. This statement also open the oppurtunity of hydrocarbon exploration activity within the southern part of Kutai Basin.